Direct-Acting Oral Anticoagulants in the Management of Cerebral Venous Sinus Thrombosis—Where Do We Stand? - Nikhil Vojjala; Supriya Peshin; Lakshmi Prasanna Vaishnavi Kattamuri; Rabia Iqbal; Adit Dharia; Jayalekshmi Jayakumar; Rafi Iftekhar; Shagun Singh; Mamtha Balla; Claudia S. Villa Celi; Ramya Ramachandran; Rishab Prabhu; et al. (Biomedicines)
Background: Cerebral venous sinus thrombosis (CVT) is a rare cause of stroke, constituting 0.5–3% of all strokes with an extremely varied spectrum of presentation, predisposing factors, neuroimaging findings, and eventual outcomes. A high index of suspicion is needed because timely diagnosis can significantly alter the natural course of the disease, reduce acute complications, and improve long-term outcomes. Due to its myriad causative factors, protean presentation, and association with several systemic diseases, CVT is encountered not only by neurologists but also by emergency care practitioners, internists, hematologists, obstetricians, and pediatricians. Discussion: Anticoagulation remains the mainstay of treatment for CVT. Heparin and warfarin previously had been the anticoagulation of choice. Recently there has been an increased interest in utilizing direct-acting oral anticoagulants in the treatment of CVT given comparable safety and efficacy with ease of utilization. However recent clinical guidelines given by multiple societies including the American Stroke guidelines and European guidelines do not include these agents so far in their treatment recommendations. Ongoing multicentric clinical trials are currently reviewing the role of these agents in both short-term as well as long-term. Our review of the literature supports the safety and reinforces the efficacy of DOAC in the treatment of CVT. Additionally, patient satisfaction has been shown to be better with the use of DOAC. In conclusion, DOAC continues to have a valid role in the management of CVT.